The world allies : a survey of nationalism, labour and worldtrade; and a remedy for wage-slavery and war - De Kay, John (Berne Bienne Zürich : Ernst Kuhn, 1917)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 1